Early exposure to macroeconomic shocks: gold boom and birth weight in Colombia - Charris Vizcaino, Carlos Andres (2017)
The human capital literature has suggested a significant role of individual capabilities in the formation of human capital. There is substantial evidence that inequalities in capacities are consequences of differences in initial endowments (e.g. birth weight). In turn, there exists a hypothesis in the epidemiological literature pointing out that fetuses are vulnerable to environmental factors, which can have a positive or negative impact on their initial endowments. Taken together, this suggests that identifying shocks that affect health at birth must be of particular interest to researchers and policy makers. Therefore, this research attempted to provide further empirical evidence to the question whether macroeconomic shocks have effect on neonatal outcomes. The evidence came from of the study of collateral effects of the 2002 surge in international gold prices on the probability of low and very low birth weight in the Colombian context. Additionally, we verified whether this effect is correlated with measures of maternal exposure to the gold boom. Because changes in the return to gold-related work are accompanied by competing income and substitution effects, we estimated the net effect of the gold boom on health at birth. Our methodology followed a difference-in- differences approach by assessing whether changes in gold world prices affect birth outcomes disproportionately in municipalities that produce more of this commodity. Using the records of vital statistics from 1998 to 2014, we find that the surge in world gold prices disproportionately reduced the incidence of low and low birth weight in gold municipalities. We also find that the shock increased fertility for less-educated mothers and decreased use of prenatal care for all mothers. We conclude that, given that women’s health behavior worsens with gold boom and that incomes are higher in this cycle, it would seem that the income effect is an important determinant of health at birth.